Exequias para cuerpos prostituidos en dos novelas latinoamericanas (Altre Modernità, 2010)
This paper reflects on the triangulation between literature, dead bodies and prostitution as a productive mechanism for studying the prostitute's body as a site of both systemic violence and potential agency in two texts of Latin American literature: La novia oscura (1999) and Qué raro que me llame Guadalupe (1999) by Myriam Laurini. This analysis was selected one fragment of each novel, where the dead bodies of prostitutes as protagonists. From these textual mapping is woven associated with different modes of production that cross symbolic scenes, with different notions of funeral rituals and "uses" of these bodies present negotiations and strategies that involve the element where ritual and staging of bodies will be highly relevant. In the speech of the body (Grosso: 2007) died of prostitutes and the threat desire are articulated within an area of edge and center simultaneously. The dead body is desired prostituted and rejected as a result of discrimination based on a structured regulatory culture, historically, between hiding and display within an exclusive system that transforms the body into something monstrous. So what are the tactics that show these bodies where they converge various covenants that are beyond the control mechanisms and acceptability?  What fears and desires that their exposure occurs at a funeral?
Keywords: cuerpos; prostitutas; exclusión; cuerpos muertos; literatura latinoamericana